2015
DOI: 10.1590/1516-635x170117-24
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nutrient manipulation to improve the performance and tibia characteristics of broilers fed oak acorn (Quercus Brantii Lindl)

Abstract: An experiment was conducted to evaluate the effects of dietary nutrients (protein, methionine, and choline) manipulation on the performance and tibia characteristics of broilers fed diets containing 15% oak acorn. A completely randomized design with five treatments and four replicates of 15 chicks each, was used. One group was fed a diet based on corn (without oak acorn) as control and other four groups were fed diets containing oak acorn with one of the following nutrient manipulation: without nutrient manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
2
9
0
1
Order By: Relevance
“…Table 3 shows that OA contains considerable levels of total phenols, including tannins. The results of chemical composition and the content of phenolic compounds of Iranian OA are in line with a recent study on this species (Houshmand et al, 2015). The effects of dietary OA level and PEG on BWG, feed intake and FCR of broilers at various phases of the study are given in Table 4.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Table 3 shows that OA contains considerable levels of total phenols, including tannins. The results of chemical composition and the content of phenolic compounds of Iranian OA are in line with a recent study on this species (Houshmand et al, 2015). The effects of dietary OA level and PEG on BWG, feed intake and FCR of broilers at various phases of the study are given in Table 4.…”
Section: Resultssupporting
confidence: 85%
“…Rezaei & Semnaninejad (2016) observed that feeding with OA reduced broiler performance when included at 100 and 200 g/kg of diet. Similarly, Houshmand et al (2015) found that using 150g/kg OA had negative consequences on broiler performance and tibia bone characteristics. In another study (Bouderoua et al, 2009), it was shown that broilers fed OA had lower bodyweight at 35 days of age.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Ainda, Alves et al (2017b) relataram que o extrato de Acacia mearnsii contém 75% de polifenóis totais, sendo o tanino o principal grupo presente nestas plantas. Taninos são componentes polifenólicos hidrossolúveis (KESHAVARZ et al, 2017) e historicamente sempre foram vistos como fator antinutricional presente nos alimentos (MEDUGU et al, 2012;HOUSHMAND et al, 2017;TOMASZEWSKA et al, 2018). No entanto, recentemente o tanino vem sendo utilizado como modulador de flora microbiana intestinal, melhorando o desempenho das aves, sendo viável seu uso em substituição a antibióticos promotores de crescimento.…”
Section: Introductionunclassified